Differences in Noradrenaline Receptor Expression Across Different Neuronal Subtypes in Macaque Frontal Eye Field - Lee, Max; Mueller, Adrienne; Moore, Tirin (Frontiers in Neuroanatomy, 2020)
Cognitive functions such as attention and working memory are modulated by noradrenaline receptors in the prefrontal cortex (PFC). The frontal eye field (FEF) has been shown to play an important role in visual spatial attention. However, little is known about the underlying circuitry. The aim of this study was to characterize the expression of noradrenaline receptors on different pyramidal neuron and inhibitory interneuron subtypes in macaque FEF. Using immunofluorescence, we found broad expression of noradrenaline receptors across all layers of the FEF. Differences in the expression of different noradrenaline receptors were observed across different inhibitory interneuron subtypes. No significant differences were observed in the expression of noradrenaline receptors across different pyramidal neuron subtypes. However, we found that putative long-range projecting pyramidal neurons expressed all noradrenaline receptor subtypes at a much higher proportion than any of the other neuronal subtypes. Nearly all long-range projecting pyramidal neurons expressed all types of noradrenaline receptor, suggesting that there is no receptor-specific machinery acting on these long-range projecting pyramidal neurons.